Um olhar sobre a obra de Acácio Gil Borsoi obras e projetos residenciais 1953-1970 - Silva, Izabel Fraga do Amaral e (2004)
This essay studies the contribution of architect Acácio Gil Borsoi (1924-), who played an important role in the consolidation of Modern Architecture in the Northeast of Brazil. The universe analyzed is constituted of 48 residential projects, houses and apartment buildings, both built and unbuilt, dating from 1953 to 1970. Considering an analogy between architecture and language, the selected projects were analyzed focusing in the process of creation